Identification of germline DICER1 mutations and loss of heterozygosity in familial Wilms tumour. Issue 6 (13th November 2015) - Palculict, Timothy Blake; Ruteshouser, E Cristy; Fan, Yu; Wang, Wenyi; Strong, Louise; Huff, Vicki
Abstract : Wilms tumour (WT), a paediatric renal cancer, is the most common childhood kidney cancer. The aetiology of WT is heterogeneous with multiple genes known to result in WT tumorigenesis. However, these genes are rarely associated with familial Wilms tumour (FWT). To identify mutations predisposing to FWT, we performed whole-genome sequencing using genomic DNA from three affected/obligate carriers in a large WT family, followed by Sanger sequencing of candidate gene mutations in 47 additional WT families to determine their frequency in FWT. As a result, we identified two novel germline DICER1 mutations (G803R and R800Xfs5) co-segregating in two families, thus expanding the number of reported WT families with unique germline DICER1 mutations. The one large family was found to include individuals with multiple DICER1 syndrome phenotypes, including four WT cases. Interestingly, carriers of the DICER1 mutation displayed a greatly increased frequency of WT development compared with the penetrance observed in previously published pedigrees. Also uniquely, in one tumour this DICER1 mutant allele (G803R) was reduced to homozygosity in contrast to the somatic hotspot mutations typically observed in tumours in DICER1 families.